The aspectual status of the verbal prefix des- in European Portuguese - Oliveira, Duarte (2021)
Some studies on the aspectual and morphosyntactic status of prefixes suggest that theircontribution to the verbal predicate is aspectual in nature. In her adjunct theory of preverbs, DiSciullo (1997, 2003, 2005) argues that prefixes are projected as adjuncts at the MorphologicalForm (MF) interface of verbal derivations and can be defined as either external or internalprefixes, depending on their projection with respect to the VP. In this approach, prefixes conformto the Adjunct Identification Principle (AIP), according to which they display specificconfigurational properties in the structure. In Portuguese, the prefix des- deserves particularattention. This prefix is theoretically defined as an external prefix and convey aspectual and nonaspectualinformation, which is external to the verbal projection. It can also impart internalaspectual information in certain senses. In the present study, the adjunct approach is reviewed andapplied to the prefix des- in Portuguese. A primary analysis shows that des- imposes someselectional restrictions on the verbal base to which it adjoins. When the semantic value of theprefix is inverse, it tends to select inherently telic verbs, and when it is negative, it usually selectsatelic verbs. In its extractive value, it is argued that des- holds the status of an internal prefix, identifying a terminative feature [+T] in the verbal derivation. A corpus analysis was laid out, which supports the formulated hypotheses.